2010
DOI: 10.1167/iovs.10-5377
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes-Induced Inhibition of Voltage-Dependent Calcium Channels in the Retinal Microvasculature: Role of Spermine

Abstract: PURPOSE.Although decentralized control of blood flow is particularly important in the retina, knowledge of the functional organization of the retinal microvasculature is limited. Here, the authors characterized the distribution and regulation of L-type voltage-dependent calcium channels (VDCCs) within the most decentralized operational complex of the retinal vasculature-the feeder vessel/capillary unit-which consists of a capillary network plus the vessel linking it with a myocyteencircled arteriole. METHODS. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
55
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(58 citation statements)
references
References 36 publications
3
55
0
Order By: Relevance
“…Electrophysiological and pharmacological studies have revealed that pericytes are electrically excitable cells [10,43,44,45]. The resting membrane potential of pericytes ranges from -32 to -70 mV [43,45] and can be modulated by different ion channels present in their plasma membrane such as Ca 2+ -activated Cl - channels (Cl Ca ) [18,46], Ca 2+ -activated K + channels (K Ca ) [45], ATP-sensitive K + channels (K ATP ) [47], inwardly rectifying K + channels (K IR ) [43,45], voltage-dependent K + channels (K V ) [45], voltage-gated Na + channels [48], nonselective cation channels [21] and transient receptor potential channels [49].…”
Section: Pericytes Are Electrically Excitable Cellsmentioning
confidence: 99%
See 4 more Smart Citations
“…Electrophysiological and pharmacological studies have revealed that pericytes are electrically excitable cells [10,43,44,45]. The resting membrane potential of pericytes ranges from -32 to -70 mV [43,45] and can be modulated by different ion channels present in their plasma membrane such as Ca 2+ -activated Cl - channels (Cl Ca ) [18,46], Ca 2+ -activated K + channels (K Ca ) [45], ATP-sensitive K + channels (K ATP ) [47], inwardly rectifying K + channels (K IR ) [43,45], voltage-dependent K + channels (K V ) [45], voltage-gated Na + channels [48], nonselective cation channels [21] and transient receptor potential channels [49].…”
Section: Pericytes Are Electrically Excitable Cellsmentioning
confidence: 99%
“…The resting membrane potential of pericytes ranges from -32 to -70 mV [43,45] and can be modulated by different ion channels present in their plasma membrane such as Ca 2+ -activated Cl - channels (Cl Ca ) [18,46], Ca 2+ -activated K + channels (K Ca ) [45], ATP-sensitive K + channels (K ATP ) [47], inwardly rectifying K + channels (K IR ) [43,45], voltage-dependent K + channels (K V ) [45], voltage-gated Na + channels [48], nonselective cation channels [21] and transient receptor potential channels [49]. Voltage-clamp experiments performed on pericytes in culture [10] or on isolated microvessels [10,44,45] show that pericytes contain L-type voltage-gated Ca 2+ channels (VGCC). However, comparative studies performed on the freshly isolated retinal microvascular complexes [44] and kidney tissue slices [45] show that VGCC-mediated changes in ionic currents are markedly (i.e.…”
Section: Pericytes Are Electrically Excitable Cellsmentioning
confidence: 99%
See 3 more Smart Citations